Margret & H.A. Rey's Curious George at the parade - Margret & H.A. Rey (1906-1996); (1898-1977); Rey, Margret; Rey, H. A. (Hans Augusto), 1898-1977.; Vipah Interactive (Boston : Houghton Mifflin, 1999)
George's curiosity creates chaos at a holiday parade.
Accelerated Reader AR
Keywords: Monkeys -- Juvenile fiction; Parades -- Juvenile fiction